Digging through history : archaeology and religion from Atlantis to the Holocaust - Freund, Richard A. (Rowman & Littlefield Publishers, 2012)
Digging through History follows rabbi and archaeologist Richard Freund's journey through some of the most fascinating archaeological sites of human history-including the mysterious Atlantis, Qumran and the Dead Sea Scrolls, and the long-buried Holocaust camp Sobibor. Each chapter takes readers through a different archaeological site, showing what we can learn about past religious life and religious faith through the artifacts found there, as well as what has given each site such strong "staying power" over time